Aeration requirement and energy consumption of reactor-composting of rose pomace influenced by C/N ratio - Ekinci, Kamil; Tosun, Ismail; Kumbul, Barbaros Salih; Sevik, Fevzi; Suluk, Kemal; Bitrak, Necati Berk (Springer, 2020)
As the composting industry develops rapidly in the world, the compost producers have focused on the efficiency of energy utilization in production without restricting the quality of compost in the forced ventilation systems. Therefore, this experimental study quantified the impacts of initial C/N ratio on aeration requirement and energy consumption due to aeration for reactor composting of rose pomace through kinetics of the process using fifteen 100-l composting reactors. The results of the study showed that initial C/N ratio significantly affected decomposition rate, compost maturity, and dry matter losses and organic matter losses (P < 0.05). The maximum decomposition rate (0.072 day(-1)) and the highest degree of progression of the composting process existed at the mixture with initial C/N ratio of 24.26. The results underlined the importance of the initial C/N of composting of rose pomace in terms of energy consumption due to aeration. In particular, more mature compost within a short time can be obtained when composting was operated with a C/N ratio of 23.7-25.8 in the expense of requiring more airflow rate, fan power, and energy consumption by aeration fan per composting material.
SULUK, KEMAL/0000-0003-1853-8872; BITRAK, Berk/0000-0002-6822-3564
Keywords: Composting; Rose pomace; Aeration; Energy requirement; Decomposition; C; N ratio